Penambahan Berat Badan antara Dua Waktu Hemodialisa pada Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa di RSD Mardi Waluyo Kota Blitar - Tri Cahyo Sepdianto; Suprajitno Suprajitno; Erna Usmiati (Journal of Ners and Midwifery, 2017)
The Interdialysis Weight Gain more than 5 % of weight dry can result in negative towards patients of them hypotension , edema , shortness of breath , lightheaded and can lead to the death .Research objectives is to find interdialysis weight gain in Chronic Kidney Disease Patients. A method in this research use descriptive design .Population in this study all patients of chronic kidney disease who get hemodialisa in installation hemodialisa RSD mardi waluyo blitar are 89 peoples , uses the technique total population. Data collection is performed by measuring weight patients after hemodialisa ago and before hemodialisa next .This research result that weight gain between the two time lightweight hemodialysis 60,7%, 12,4% on average, and 26,9% of danger . Extra weight category of danger caused because patients do not adhere to diet. Recommendations from the study is expected to become an evaluation for installation hemodialisa RSD Mardi Waluyo Blitar to increase intervention on patients who get hemodialisa .